Pemikiran Ekonomi Islam tentang Riba dan Implikasinya pada Stabilitas Keuangan di Era Kontemporer - Hasanatun Fitri; Artika Tri Septia; Siti Rahma Mutiara; Ahmad Wahyudi Zein (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the concept of riba in Islamic economic thought and its implications for financial stability in the contemporary era. The research employs a qualitative descriptive method by reviewing primary sources, including the Quran, Hadith, and scholars' fatwas, as well as secondary sources such as academic literature and previous research on riba and Islamic finance. The findings reveal that riba has a significant impact on economic instability and social inequality. Meanwhile, profit-sharing systems and other Islamic financial instruments offer sustainable solutions for maintaining financial stability. This research contributes to the understanding of Islamic economic principles and their practical application in addressing modern financial challenges.